Exploring emotional, behavioural, and cognitive dimensions of young citizens’ political engagement in uncertain times - Κατερίνα Καραγεώργου; Άννα Μαντόγλου; Δημήτρης Καλαμάρας (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2024)
Political engagement (PE) is approached as a complex concept that incorporates cognitive, behavioural, and emotional aspects. This study aims to investigate the suggested typology of PE (partisan, apartisan, stand-by, apolitical, antipolitical), and to identify those variables (cognitive, emotional, behavioural) that contribute to the appearance of each type. Surveys are conducted in the UK, France, and Greece, as these countries both represent and experience different types of crises. Participants (N=1.005), from 18 to 35 years old, were classified into the types according to their self-positioning on PE typology. Five models of logistic regression were applied to our samples. The five types of PE were used as the criterion variables, whereas the emotional (emotions towards politics: enthusiasm, anxiety, aversion, disgust, disappointment, indifference; emotions towards crisis: fear/frustration, trust/optimism, anger/indignation), the cognitive (political interest: interest in politics, interest in societal issues), and the behavioural dimensions (political participation: non-digital political activism, activities of socio-political concerns, digital political activism, normative collective action, active political counter-argumentation, and pro-social activism) as predictors. Results showed that different forms of political interest, different repertoires of political behaviours, and different sets of emotions contribute to the appearance of each type of PE. Furthermore, PE types are interpreted through the complexity of modern societies. Especially for apolitical and anti-political types of engagement, discussion suggests that they could be considered as forms of political identities in post-democratic societies of developing crises and uncertainty.